Effectiveness of dialectical behavior therapy skills training group for adults with borderline personality disorder. Issue 7 (5th April 2021) - Heerebrand, Sharon L.; Bray, Jemma; Ulbrich, Christine; Roberts, Rachel M.; Edwards, Suzanne
Abstract: Objective: This study evaluated the effectiveness of the Dialectical Behavior Therapy Skills Training Group (DBT‐ST) component of DBT. Method: Participants ( N  = 114) attended an 18–20‐week DBT‐ST. The study utilized a quasi‐experimental design with a within‐persons control group for a measure of borderline personality disorder (BPD) symptoms (at referral), and emergency department (ED) presentations, and psychiatric bed‐days (both assessed for 6 months pre‐ and post‐intervention). Primary outcomes were the number of BPD symptoms, psychological distress, depression, rate of ED presentations, and psychiatric inpatient bed‐days. Results: After completing DBT‐ST, participants had reduced BPD symptoms, psychological distress, and depression ( p  < 0.001). The waitlist control group showed no improvement in BPD symptoms ( p  = 0.085). The rate of ED presentations was reduced ( p  = 0.001). There was no reduction in psychiatric inpatient bed‐days ( p  = 0.160), likely due to insufficient power. Conclusions: DBT‐ST participation in addition to treatment‐as‐usual is an effective treatment for people with BPD.